A Comparative Study of English Education Department - Muhamad, Hujaefa Hi.; Ibrahim, Ratu Balgis (Newinera Publisher, 2025)
The comparative study of English Department students' achievement at Khairun University explores significant variations in speaking skills among 300 students from the 1st, 3rd, and 5th semesters. This research uses quantitative-descriptive methods. The research employs questionnaires and interviews to assess demographic information, speaking challenges, influencing factors, and supporting elements. Findings reveal an average age of 19.2 years impacting speaking achievement, with a noteworthy correlation between proficiency, Grade Point Average (GPA), and academic grades. Higher-than-average GPA and grades correspond to enhanced speaking skills. Additionally, parents' educational backgrounds and occupations significantly influence speaking achievement, with 17.1% having a Bachelor's degree and 53.6% working as farmers. Students from educated and employed families excel in speaking English. Study habits indicate limited commitment, with most students spending less than an hour per week practicing speaking. English speaking courses show advantages for participants, particularly those dedicating more hours to study. The study emphasizes the need to enhance students' awareness and motivation for developing speaking proficiency beyond academic contexts. Overall, the research provides insights for targeted educational interventions to improve students speaking skills in English Department at Universitas Khairun.